Structural and optical properties of Eu3+ and Mg2+ doped LiTaO3 obtained via the polymeric precursor method - Gasparotto, G. [UNESP]; Cebim, Marco Aurelio [UNESP]; Góes, M. S. [UNESP]; Davolos, Marian Rosaly [UNESP]; Paiva-Santos, C. O. [UNESP]; Varela, José Arana [UNESP]; Zaghete, M. A. [UNESP] (My University, 2009)
This work reports on the pure lithium tantalate (LiTaO3), europium (III)-doped LiTaO3 and magnesium (II)-europium (III)-doped LiTaO3 preparared by the polymeric precursor method, using four different powered samples of Eu3+ ion concentrations 0.1 to 1at %. Structural and optical properties of powders have been studied. The different possible sites occupied by the rare earth were examined. The phase contents and lattice parameters were studied by the Rietveld method and the structural disorder in the LiTaO3 host caused by Eu3+ ions was analyzed. Results indicated LiTaO3 free of secondary phases at 650°C and the photoluminescence (PL) emission spectra showed the characteristic sharp emission bands given by Eu3+ ions when they are excited at a wavelength of 399 nm. An increase of dopants contents caused a non-homogeneous broadening and showed a slightly larger one when Mg was added. A displacement of the transition 5D0-7F0 to shorter wavelengths as function of Eu3+ concentration was also noticed.
Keywords: Ion concentrations; Lithium tantalate; Photoluminescence emission; Polymeric precursor methods; Secondary phasis; Shorter wavelength; Structural and optical properties; Structural disorders; Ceramic materials; Doping (additives); Emission spectroscopy; Europium; Exhibitions; Optical properties; Rietveld method; Polymers